Embodiment of the Principle of Economy in Media Discourse (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The author discusses the phenomena of discourse and media discourse. Various interpretations of the term «media discourse» are presented, the main characteristics of a media discourse are considered, in particular, the types of media discourse, its differential features and typological properties. The media discourse is described as a phenomenon that not only complements, distorts or reproduces reality, but projects that reality that reflects collective ideas about it. The article describes the functions of the media that are implemented in the process of a communicative act. The subfunctions of the acting function of the media, embodied in the media discourse, are also listed, three basic categories of speech exposure are identified. The analysis of the universal category of media discourse (persuasiveness) is provided.